VD_FINDINFO HC / 2012 / 401 vom 4. Mai 2012 - VD Tribunal cantonal (2012)
DÉCISION INCIDENTE, PROROGATION DE FOR, VENTE, COMPÉTENCE, EXCEPTIONMOYEN DE DÉFENSE | 21 al. 1 let. a LFors, 22 al. 1 let. a LFors, 237 CPC (CH), 308 al. 2 CPC (CH), 319 CPC (CH), 32 al. 1 let. a CPC (CH), 320 CPC (CH), 322 al. 1 CPC (CH), 35 al. 1 let. a CPC (CH), 406 CPC (CH)